Nitrogen availability increases in a tundra ecosystem during five years of experimental permafrost thaw. (26th February 2016) - Salmon, Verity G.; Soucy, Patrick; Mauritz, Marguerite; Celis, Gerardo; Natali, Susan M.; Mack, Michelle C.; Schuur, Edward A. G.
Abstract: Perennially frozen soil in high latitude ecosystems (permafrost) currently stores 1330–1580 Pg of carbon (C). As these ecosystems warm, the thaw and decomposition of permafrost is expected to release large amounts of C to the atmosphere. Fortunately, losses from the permafrost C pool will be partially offset by increased plant productivity. The degree to which plants are able to sequester C, however, will be determined by changing nitrogen (N) availability in these thawing soil profiles. N availability currently limits plant productivity in tundra ecosystems but plant access to N is expected improve as decomposition increases in speed and extends to deeper soil horizons. To evaluate the relationship between permafrost thaw and N availability, we monitored N cycling during 5 years of experimentally induced permafrost thaw at the Carbon in Permafrost Experimental Heating Research (CiPEHR) project. Inorganic N availability increased significantly in response to deeper thaw and greater soil moisture induced by Soil warming. This treatment also prompted a 23% increase in aboveground biomass and a 49% increase in foliar N pools. The sedge Eriophorum vaginatum responded most strongly to warming: this species explained 91% of the change in aboveground biomass during the 5 year period. Air warming had little impact when applied alone, but when applied in combination with Soil warming, growing season soil inorganic N availability was significantly reduced. These results demonstrate that there is a strong positive relationship between the depth of permafrost thaw and N availability in tundra ecosystems but that this relationship can be diminished by interactions between increased thaw, warmer air temperatures, and higher levels of soil moisture. Within 5 years of permafrost thaw, plants actively incorporate newly available N into biomass but C storage in live vascular plant biomass is unlikely to be greater than losses from deep soil C pools.